A conceptual model of posttraumatic growth of nursing students with a disabled parent - Yuli Li; Huayu Bai; Fenglan Lou; Fenglin Cao (Elsevier, 2019)
Objectives: To examine a conceptual model of posttraumatic growth (PTG) with the inclusion of family resilience as a mediator, and social support, individual resilience, maternal care, and family members' intimacy after trauma as protective factors. Methods: A cross-sectional questionnaire survey was carried out in a sample of 134 college nursing students who had a parent with a non-congenital disability. The Socio-demographic Information Questionnaire, the Chinese version of Perceived Social Support Scale (PSSS), 10-item Connor-Davidson Resilience Scale (CD-RISC10), Parental Bonding Instrument (PBI), Family Resilience Assessment Scale (FRAS) and the Posttraumatic Growth Inventory (PTGI) were used to collect data. Results: Results showed that social support, individual resilience, maternal care, and family members' intimacy after trauma positively predicted family resilience (β = 0.41, 0.20, 0.20, 0.22, all P＜0.01), respectively, and indirectly predicted PTG through family resilience. Family resilience positively predicted PTG (β = 0.25, P＜0.01). Moreover, individual resilience directly positively predicted PTG (β = 0.25, P＜0.001). Conclusions: Family resilience could facilitate PTG in nursing students in the face of parental disability. Interventions to promote PTG among college nursing students who have experienced parental disability should consider individual or family resilience-based intervention. Keywords: Family, Parenting, Posttraumatic growth, Psychological resilience, Social support